Influence of converged newsroom platforms to the practice of professional journalism by the Herald and Daily News - Nyabunze, Susan (Midlands State University, 2017)
The study sought to establish the influence of newsroom convergence to the practice of professional journalism by The Herald and daily News. The study sought to establish how the two publications which have opposed views are adapting to newsroom convergence and with what effect the development plays in the practice of professional journalism. The study was mainly qualitative and data was taped from the targeted population using qualitative data collection methods. The researcher made use of interviews, questionnaires and focus group discussions to obtain data from the CEO’s, editors, journalists and online audiences of the two publications. In addition, the study employed convenience and purposive sampling techniques that are non-probability and purely qualitative. The study was guided by the following theories namely social shaping of technology, diffusion of innovations and revisiting the public sphere. The findings were analyzed and presented in the study as well as the proposed recommendations. The study deduced that The Herald and daily News are influenced by newsroom convergence pausing both negative and positive effects on professional journalism. Albeit the fact that the two are owned and controlled differently, both share the same responses to converged newsroom platforms. Newsroom convergence has brought many changes to both publications in as much as the daily newsroom operations are concerned. Again the study deduced that converged newsroom platforms have economic benefits but impinge on professionalism of journalists.